Transient stability enhancment by DSSC with fuzzy supplementary controller. - Khalilian, Mansour (Journal of electrical engineering & technology)
The distributed flexible alternative current transmission system (D-FACTS) is a recently developed FACTS technology. Distributed static series compensator (DSSC) is one example of D-FACTS devices. DSSC functions in the same way as a static synchronous series compensator (SSSC), but is smaller in size, lower in price, and possesses more capabilities. Likewise, DSSC lies in transmission lines in a distributed manner. In this work, we designed a fuzzy logic controller to use the DSSC for enhancing transient stability in a two-machine, two-area power syatem. The parameters of the fuzzy logic controller are varied widely by a suitable choice of membership function and parameters in the rule base. Simulation results demonstarte the effectiveness of the fuzzy controller for transient stability enhancement by DSSC.